Countryside Middle Class Growth in Brazil and its Impacts on Domestic Tourism - Anderson Pereira Portuguez; Vanda Aparecida da Silva Alves (Via@)
This work discusses two of the several historical processes responsible for formation and current spatial distribution of the Brazilian middle classes, and shows that official demographic data highlight that over the last 30 years there has been a process of quantitative growth of this social stratum. There is still much to be studied about the Brazilian middle class and, in this sense, this article is a contribution to the efforts many researchers have been making to understand it.In a previous study (Portuguez, 2010a), we have already argued that without middle class there is no possibility for capitalism to maintain itself using the framework it has taken in this present time, neither any possibility of a significant economic contribution through tourism, once the clientele that comprises the controversial “mass tourism” is exactly the middle class. This social stratum is the ground of worldwide consumer mass and therefore the target of the most varied advertising campaigns, including those that promote tourist destinations. We affirm :It is upon middle class structure of life that modern (or westernized) Western States were able to build and consolidate themselves through social institutions that give identity to this social stratum. Without this segment of the population, the informational economy does not grow and, of course, what meaning would trade have without avid consumerist demand ? (Portuguez, 2010a, p. 22)This text tries at first to understand concepts related to middle class, its spatial distribution and quantitative increase, especially from the late twentieth and early twenty-first century. Then it reflects on the impacts that these phenomena (location and numeric growth) have on tourism activity, particularly on destinations of regional importance, outside of the great circuits massively promoted by media and big tourism business.